PERILAKU INVESTOR MUSLIMAH DI PASAR MODAL SYARIAH DI LAMPUNG - Magdalena, Betty; Susanti, Susanti; Yanti, Yuli (Jurnal Bisnis Darmajaya, 2018)
Investment is a sacrifice performed by an investor, regardless of the gender of those investors because they expect is to get benefits in the future. Therefore, investment decisions are taken by an investor should be with careful consideration. Behavior of a much needed investors in taking the decision to invest. Many factors influence the decisions of investors in investing. One of the factors that affect the behavior of investors, namely factors of psychology. The purpose of this research was to describe the behavior of investors in the capital markets Shariah Muslim women in Lampung. Then the next will be in related analysis how the behavior of Muslim investors against investment decision-making. Population and sample in this research is the Muslim investors invest on Sharia capital market in Lampung. The results of this research show that the Muslim investors invest on Sharia capital market in Lampung dare to take risks when investing in syariah capital market in Lampung. Investors in the capital markets Shariah Muslim women in Lampung likely not behaved social interaction, but Muslim investors are more likely to behave emotion, familiarity and representativeness. Keywords — Behavior of Muslim Investors, Investment Decisions and Psychological Factors ABSTRAK Investasi merupakan suatu pengorbanan yang dilakukan oleh seorang investor, tanpa melihat gender dari investor tersebut karena yang mereka harapkan adalah untuk mendapatkan keuntungan dimasa depan. Oleh karena itu keputusan investasi, yang diambil oleh investor harus dengan pertimbangan yang matang. Perilaku seorang investor sangat dibutuhkan dalam mengambil keputusan berinvestasi. Banyak faktor yang mempengaruhi keputusan investor dalam berinvestasi. Salah satu faktor yang mempengaruhi perilaku investor yaitu faktor psikologi. Tujuan penelitian ini untuk menggambarkan perilaku investor muslimah pada pasar modal syariah di Lampung. Kemudian selanjutnya akan di analisis terkait bagaimana perilaku investor muslimah terhadap pengambilan keputusan investasi. Populasi dan sampel dalam penelitian ini adalah para investor muslimah yang berinvestasi pada pasar modal syariah di Lampung. Hasil penelitian ini menunjukkan bahwa  investor  muslimah yang berinvestasi pada pasar modal syariah di Lampung berani untuk mengambil risiko saat berinvestasi pada pasar modal syariah di Lampung. Investor  muslimah pada pasar modal syariah di Lampung cenderung   tidak   berperilaku   social   interaction,   akan   tetapi   investor muslimah lebih cenderung berperilaku emotion, familiarity dan representativeness. Kata Kunci — Perilaku investor muslimah, keputusan investasi dan faktor psikologis.